"Green Marketing": An analysis of definitions, strategy steps, and tools through a systematic review of the literature. (1st November 2017) - Dangelico, Rosa Maria; Vocalelli, Daniele
Abstract: Over the past decades, environmental sustainability has raised at the top of the international political agenda and has been recognized as a key driver of innovation. As a result, the number of companies developing green products has been rapidly growing and consumers have shown an increasing interest for these products. Thus, understanding the main characteristics of green products, identifying factors affecting their price and consumers' willingness to pay more for them, sales channels and promotional tools (the 4Ps of Green Marketing) would be very useful for companies aiming at designing, developing and marketing green products. For this reason, deeply understanding Green Marketing would foster, on the one hand, cleaner production through the development of green products and, on the other hand, sustainable consumption through the successful marketing of them. To this aim, this study reviews the body of knowledge on the topic, through a systematic review of the literature. Specifically, this paper analyzes: 1) the dominant definitions of Green Marketing (and related concepts) and their evolution over time, 2) the different steps to build a Green Marketing Strategy, and 3) the characteristics of Green Marketing Mix elements. After searching for academic publications in three databases (EBSCO, Scopus, and Web of Science) and selecting publications based on their relevance for the stated aims, 114 studies have been included in the review. Results show that the definition of Green Marketing has changed over time according to the growing relevance of environmental sustainability. Regarding the Green Marketing Strategy, several ways of segmenting consumers have been identified; studies converge in giving greater relevance to green brand positioning rather than to green product positioning and many of them see it as a chance of differentiation. Referring to the Green Marketing Mix, results show that: many types of green products exist; consumers are willing to pay a premium price according to products' functional attributes or their responsibility towards the natural environment; closed-loop supply chain and reverse logistics play a key role; a careful definition of advertisement contents is essential and ecolabels can be important tools. This study provides an in-depth analysis and synthesis of the body of knowledge so far produced in the field of Green Marketing and, as such, it has important implications for managers, scholars, and students. Highlights: A systematic review of studies on Green Marketing is conducted. The number of studies on the topic is growing fast over time. Definitions of Green Marketing and related concepts are reported. Features of Green Marketing Strategy steps are provided. Characteristics of Green Marketing Mix elements are analyzed.